THE RELATIONSHIP OF WORK LIFE BALANCE WITH CAREER LEVEL ON WOMEN EMPLOYEES IN PDAM TIRTA JENEBERANG GOWA - Adiva Arsil; M. Ikhwan Maulana Haeruddin, Agung Widhi Kurniawan, Chalid Imran Musa, Uhud Darmawan Natsir (ADISAM Publisher, 2022)
The balance between personal life & work where the balance between work and life according to Lockwood (2003) argues that work life balance is a state of balance between the same demands for daily life and at work. In their careers, women tend to look for positions that they think are more comfortable to balance between home and work life even though their position at work is not at the top of the organizational hierarchy. This study aims to determine whether the relationship between work life balance and career path for female employees at PDAM Tirta Jeneberang Gowa. This study uses a semi-structural qualitative method by using an interview guide where this interview is conducted directly to the subject.